Regenerating drylands in response to a changing climate - Gonsalves, Julian Francis; Wilson John Barbon; Chan Myae; Yinn Minn Latt (2018)
With support from IDRC and CCAFS Southeast Asia, IIRR and its local NGO partners is implementing Climate-Smart Villages (CSVs) to demonstrate community-based adaptation in agriculture in different agroecological zones in Myanmar. This primer is based on IIRR baseline studies as well as desk research that IIRR commissioned to develop the profile of Nyaung Oo CSV. The purpose of this primer is to provide the reader background information as to the agriculture, livelihoods, nutrition, gender and climate change context of the CSV.